Differential Roles of TREM2+ Microglia in Anterograde and Retrograde Axonal Injury Models - Manich, Gemma; Gómez-López, Ariadna Regina; Almolda, Beatriz; Villacampa, Nàdia; Recasens, Mireia; Shrivastava, Kalpana; González, Berta; Castellano, Bernardo (Frontiers in Cellular Neuroscience, 2020)
Microglia are the main immune cells of the central nervous system (CNS), and they are devoted to the active surveillance of CNS during homeostasis and disease. In the last years, the microglial receptor Triggering Receptor Expressed on Myeloid cells-2 (TREM2) has been defined to mediate several microglial functions, including phagocytosis, survival, proliferation and migration, and to be a key regulator of a new common microglial signature induced under neurodegenerative conditions and aging, also known as disease-associated microglia (DAM). Although microglial TREM2 has been mainly studied in chronic neurodegenerative diseases, few studies address its regulation and functions in acute inflammatory injuries. In this context, the aim of the present work is to study the regulation of TREM2 and its functions after reparative axonal injuries, using two-well established animal models of anterograde and retrograde neuronal degeneration: the perforant pathway transection (PPT) and the facial nerve axotomy (FNA). Our results indicate the appearance of a subpopulation of microglia expressing TREM2 after both anterograde and retrograde axonal injury. TREM2+ microglia were not directly related to proliferation, instead they were associated to more specific recognition and/or phagocytosis of myelin and degenerating neurons, as assessed by immunohistochemistry and flow cytometry. Characterization of TREM2+ microglia showed expression of CD16/32, CD68 and occasional Galectin-3. However, specific singularities within each model were observed in P2RY12 expression, which was only downregulated after PPT, and in ApoE, where de novo expression was detected only in TREM2+ microglia after FNA. Finally, we report that pro-inflammatory or anti-inflammatory cytokine microenvironment, which may affect phagocytosis, did not directly modify the induction of TREM2+ subpopulation in any injury model, although it changed TREM2 levels due to modification of the microglial activation pattern. In conclusion, we describe a unique TREM2+ microglial subpopulation induced after axonal injury, which is directly associated to phagocytosis of specific cell remnants and show different phenotypes, depending on the microglial activation status and the degree of tissue injury.